Sistematização na montagem de carteira de investimentos utilizando indicadores fundamentalistas em ações no mercado de capitais brasileiro - Giraldi, Micheli Franceis Faoro (2019)
This paper will use the set of appliances proposed by Rojo (2014), and from this instrument will be proposed the systematization for the choice of assets to be invested. As for its nature, this work is an applied research, aiming to be exploratory, with quantitative and qualitative approach, using bibliographic and documentary research. This research seeks to answer the following research problem: Through the tools proposed by Rojo (2014), how to systematize the application to customize an investment portfolio according to the filters that meet the objectives of each investor? In order to systematize investment portfolios based on fundamentalist analysis, taking into account the profile and objective of each investor, based on the filters, which are established through a questionnaire. The end result of the work was the presentation of flowcharts with step by step for investor decision making according to their profile, conservative, moderate or aggressive, and their objectives that were determined by the questionnaire.